2019
DOI: 10.1590/1414-431x20198334
|View full text |Cite
|
Sign up to set email alerts
|

Systemic injection of an H4 receptor agonist induces a decrease in CREB and pCREB levels in the cerebellar vermis and prefrontal cortex in mice

Abstract: Studies have shown that an injection with the histamine H4 receptor agonist VUF-8430 modulates emotional memory processes. In the present study, the aim was to verify if intraperitoneal ( ip ) injection of VUF-8430 (500 ng/kg) in mice affects the synthesis of proteins required for memory consolidation processes by activating the phosphorylation of CREB (pCREB) in classical structures linked to emotional memory (prefrontal cortex, amygdala, and hippocampus) and the cerebellar vermis, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In our laboratory, we demonstrated that VUF 8430 impaired emotional memory consolidation in mice via the cerebellar vermis, regardless of whether the proposed activities were related to anxiety, as in the elevated plus maze, or related to fear, as in an inhibitory avoidance task [15]. Furthermore, a decrease in protein expression in the cerebellar vermis was verified by CREB and phosphorylated CREB levels, which corroborates these deficits [16].…”
Section: Introductionsupporting
confidence: 63%
“…In our laboratory, we demonstrated that VUF 8430 impaired emotional memory consolidation in mice via the cerebellar vermis, regardless of whether the proposed activities were related to anxiety, as in the elevated plus maze, or related to fear, as in an inhibitory avoidance task [15]. Furthermore, a decrease in protein expression in the cerebellar vermis was verified by CREB and phosphorylated CREB levels, which corroborates these deficits [16].…”
Section: Introductionsupporting
confidence: 63%
“…Activation of H4R leads to inhibition of CREB in the cerebellar vermis and prefrontal cortex (Fernandes & Serafim, 2019). Also, H4R targets and inactivates the downstream extracellular signal-regulated kinase (ERK)-CREB pathway (Sanna, Mello, Masini & Galeotti, 2018).…”
Section: H4r and Neural Excitabilitymentioning
confidence: 99%
“…H4R antagonists inhibit vestibular neuron activity (Desmadryl et al, 2012), suggests H4R involves in vestibular neuron excitability. Agonists or antagonists target H4R are commonly used to assess the function of H4R in some behavioral and disease phenotypes (Fernandes & Serafim, 2019;Fernandes, Serafim, Gianlorenco & Mattioli, 2017;Sanna, Borgonetti, Masini & Galeotti, 2020;Zhou et al, 2019). Recently years, H4R KO mice were also applied to investigate the behavioral phenotype and its neural function (Sanna, Ghelardini, Thurmond, Masini & Galeotti, 2017).…”
Section: H4r and Neural Excitabilitymentioning
confidence: 99%